Prekmurska slovenska slovnica = Vend nyelvtan: Vend nyelvtan - Pavel, Avgust (University of Maribor Press, 2013)
Prekmurje Slovene Grammar. August Paul was born on August 28, 1886 in Cenkova and died on January 2, 1946 in Szombathely. He was the first scientist from Prekmurje, a linguist, literary historian, ethnologist, poet and writer, a tireless cultural mediator between Hungarians and Slovenes, a faithful son of two nations. "The Prekmurje Slovene language is standardized and prescribed in my grammar for the first time, so I am aware that it is not without errors. I apologize to the experts for these inevitable beginner problems and other inaccuracies. By requesting to approve it as a textbook for Prekmurje elementary, secondary, and vocational secondary schools, the Hungarian Educational Society of the Slovenian Krajina suggested in the autumn of 1941 that it was urgent to write and publish the Prekmurje-Slovene Grammar. It is for this reason that I submit the manuscript and follow any comments and advice I have given, and for that reason I have handed over three copies of the manuscript to the management of the First Graduate Public Education Administration, who will submit my comments at the request of Your Highness to the Highly Honored Commission on Education. Official reviewers may be University Professor Dr. István Kniezsa, un inverted professor dr. László Hadrovics as a connoisseur of general Slavic linguistics and Rector of Dominican Theological College, dr. Domonkos Warrior (XIV District Szent Domonkos u. 3), the titular principal of the Royal School District, Sándor Mikola, and outside Budapest the papal prelate and canon of dr. Ferenc Rogács (Sombotel), who published many works in Prekmurje. These are Prekmurje people and scholars who know the Prekmurje Slovene language." August Pavel (Letter to the Textbook Commission of the National Council for Public Education in Budapest)